Chironomid counts for the Late-glacial record of Old Buckenham Mere (UK) - Stefan Engels; Chris Francis; Ian P Matthews; Adrian P Palmer; Anne-Lise Jourdan; Katy Flowers; Ian Candy (PANGAEA, 2025)
This dataset provides the chironomid counts for the Late-glacial sediment sequence retrieved from Old Buckenham Mere (UK) in 2019. The counts are presented against depth (m). A total of 119 samples were counted. The chironomid record provides information about lake ecosystem development and was used to quantitatively infer past July air temperatures. Cores were retrieved from the current fen using a 1-m long Russian corer during field work in May 2019. Weighed samples were obtained from the core and processed in the laboratory (Royal Holloway University of London, UK). The laboratory protocol included treatment with KOH followed by a first phase of sieving. The residues were subsequently submerged in an ultrasonic bath for 2-5 seconds, followed by a second phase of sieving. Chironomid head capsules were then hand picked from the residues and mounted on permanent microscope slides using Hydromatrix™ mounting medium. Specimens were identified with reference to Brooks et al. (2007).